2018
DOI: 10.20546/ijcmas.2018.704.372
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crop Residue and Potassium Management on Yield, Quality, Nutrient Uptake and Nutrient Use Efficiency by Mungbean in Maize (Zea mays L.)-Wheat (Triticum aestivum L.)-Mungbean Cropping System

Abstract: A field experiment was conducted during 2014-15 and 2015-16 on Research Farm of Division of Agronomy, IARI at New Delhi to evaluate Influence of crop residue and potassium management on yield, quality, nutrient uptake and K use efficiencies of mungbean in maize-wheat-mungbean cropping system. The experiment consisted of 15 treatment combinations with three crop residues [no crop residue, crop residue incorporation and fungal consortium incorporation] and five potassium management practices [control, KSB, 100 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
4
3
0
Order By: Relevance
“…The relationship between grain yield and the N contained in aboveground biomass at physiological maturity provides a measure of PEN across a wide range of production environments. Similar results have been reported by Meena et al (2018) [8] . The nutrient internal use efficiency is defined as amount of grain yield produced per unit of nutrient taken up by the plant (Yang et.…”
Section: Efficiencies Of Applied Nutrientssupporting
confidence: 93%
“…The relationship between grain yield and the N contained in aboveground biomass at physiological maturity provides a measure of PEN across a wide range of production environments. Similar results have been reported by Meena et al (2018) [8] . The nutrient internal use efficiency is defined as amount of grain yield produced per unit of nutrient taken up by the plant (Yang et.…”
Section: Efficiencies Of Applied Nutrientssupporting
confidence: 93%
“…This might be due to increased fertility levels by continuous availability of nutrients released from organic manure. These results are in agreement with Prasad (2019) and Meena et al (2012). The minimum number of days to maturity was recorded under no manure.…”
Section: Days Taken To Maturitysupporting
confidence: 91%
“…Increased yield of green gram, along with higher net returns and B:C ratio was found when wheat residues were incorporated with a fungal consortium [8]. The residue incorporation in all tillage systems like zero, reduced and conventional systems resulted in significantly improved wheat grain yield, productivity of wheat and rice, OC content of soil and B:C ratio under rice-wheat cropping system [9]. "The crop establishment and residue management (CERM) impact on grain yield in rice-chickpea, rice-lentil and rice-safflower, ricelinseed, rice-mustard production systems revealed that ZTDSR (zero-till direct seeded rice) along with crop residue retention can be viable production systems with higher productivity" [10].…”
Section: Effect Of Crop Residues Management On Crop Productivitymentioning
confidence: 98%